Incentives, search engines, and the elicitation of subjective beliefs: Evidence from representative online survey experiments - Elisabeth Grewenig; Philipp Lergetporer; Katharina Werner; Ludger Woessmann (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
A large literature studies subjective beliefs about economic facts using unincentivized survey questions. We devise randomized experiments in a representative online survey to investigate whether incentivizing belief accuracy affects stated beliefs about average earnings by professional degree and average public school spending. Incentive provision does not impact earnings beliefs, but improves school-spending beliefs. Response patterns suggest that the latter effect likely reflects increased online-search activity. Consistently, an experiment that just encourages search-engine usage produces very similar results. Another experiment provides no evidence of experimenter-demand effects. Overall, results suggest that incentive provision does not reduce bias in our survey-based belief measures.
Keywords: D83; C83; C90; 330; beliefs; incentives; online search; survey experiment